POTENSI TOKSISITAS EKSTRAK ETANOL DAUN SALAM DAN KEJI BELING DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Alfin Surya; Andre Ajis Saputra; Hesti Marliza; Zaiyar (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
A natural product that contains compounds that act as anticancer can be detected by conducting a preliminary test, namely the toxicity test. One of the methods in the Toxicity test is the BSLT test method as an initial step in the search for new anticancer compounds. The toxicity value of this method has been shown to correlate with cytotoxicity. anticancer compound. and can show a correlation to a specific anticancer. Bay plants contain saponins, triterpenoids, flavonoids, polyphenols, alkaloids, tannins, and essential oils consisting of sesquiterpenes, lactones, and phenols, which can be used as an alternative to prevent dyslipidemia, antioxidants, anti-inflammatories, antidiabetics, antidiarrheals and antihypertensives. Vile shard plant. contains various kinds of secondary metabolites and chemical substances such as potassium, sodium, silicic acid, calcium, saponins, alkaloids, polyphenols and flavonoids which act as antioxidants and can inhibit the growth and development of cancer cells. The purpose of this study was to compare the toxic effects of the ethanol extract of bay leaves and keji shard leaves on Artemia Salina Leach larvae. The type of research used was quantitative. The novelty of this research is to get the thick extract using sonification so that the time is more efficient compared to just doing maceration which takes longer. The results showed that the extracts of bay leaves and keji shard leaves are very toxic so they have the potential to be anticancer, as evidenced by the LC50 values of the bay leaf and koji shard leaf extracts which were 32.35 ppm and 194 ppm. From the LC50 value, bay leaves have higher toxicity than bitter shard leaves. The results obtained in this study can be used as an illustration for further research for the export of natural plant materials that have the potential as anticancer drugs.